KONTRIBUSI PSIKOLOGI DALAM DUNIA PERADILAN: DIMANA DAN MAU KEMANA - Meliala, Adrianus (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2008)
This paper explores the contribution of psychology to the judiciary, more specifically to the courtroomsituation. The writer argues that despite important contributions to other stages within the criminaljustice system, this judicial stage can be regarded decisive. The writer also provides argument as to whypsychological application to the judiciary is also named forensic psychology. Several approaches in thecurrent situation relating contribution of psychology to the judicial system are discussed by the writer. Somelook progressive while others seem to be rather backward. Discussion is extended to future situations facedby the contribution of psychology, and to the steps that should be undertaken.
Keywords: judicial system, court-room, psychological contribution, forensic